2022
DOI: 10.1080/22221751.2022.2140607
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, cell death, and cytokines in K. pneumoniae infection: therapeutic perspectives

Abstract: Klebsiella pneumoniae is a notorious nosocomial pathogen causing a wide range of infections. The increasing trend of antimicrobial resistance obtained by the species immensely highly challenges the clinical treatment, representing a large threat to the global health care network. In particular, the recent convergence of multidrug resistance and hypervirulence in K. pneumoniae further worsens clinical outcomes, resulting in high mortality. Developments of new therapeutics becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 149 publications
(194 reference statements)
0
18
0
Order By: Relevance
“…Capsular polysaccharides and LPS can form a complex on the surface of the bacterium through a complement‐mediated chain reaction that mediates bacterial evasion or resistance to be killed by the host's natural immunity (Krzyżewska‐Dudek et al., 2022). K. pneumoniae can be classified into 82 K serotypes according to the difference in capsular polysaccharides (K antigens), of which serotypes K1, K2 and K5 are closely related to serious infectious diseases in humans and animals (S. Wei, Xu, Chen, & Zhou, 2023), particularly K1 and K2 serotypes, which are highly virulent (Zhu et al., 2021). In this study, the magA gene was detected in K. pneumoniae ELD strains, which is a gene specific to K. pneumoniae serotype K1 (Fang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Capsular polysaccharides and LPS can form a complex on the surface of the bacterium through a complement‐mediated chain reaction that mediates bacterial evasion or resistance to be killed by the host's natural immunity (Krzyżewska‐Dudek et al., 2022). K. pneumoniae can be classified into 82 K serotypes according to the difference in capsular polysaccharides (K antigens), of which serotypes K1, K2 and K5 are closely related to serious infectious diseases in humans and animals (S. Wei, Xu, Chen, & Zhou, 2023), particularly K1 and K2 serotypes, which are highly virulent (Zhu et al., 2021). In this study, the magA gene was detected in K. pneumoniae ELD strains, which is a gene specific to K. pneumoniae serotype K1 (Fang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae has the ability to activate autophagy, promoting the formation of neutrophil extracellular traps (NETs), a process that enhances the bactericidal effect of neutrophils. 21 However, K. pneumoniae also possesses the capability to interfere with the fusion of phagosomes and lysosomes, creating a relatively safe habitat within host cells.…”
Section: Interaction Between K Pneumoniae Infectio...mentioning
confidence: 99%
“…Xu also reported that K. pneumoniae NdpA, which suppresses early hot in ammation, can be degraded by its host through ubiquitination [39]. Additionally, the association between host autophagy and ubiquitination initiated by K. pneumoniae infection was investigated [40]. A small ubiquitin-related modi er(SUMO) can be involved in various biological processes, including immunopathology and in ammation [41,42] dependent on the NF-κβ activation [43].…”
Section: Genotypingmentioning
confidence: 99%